2015
DOI: 10.1002/jbm.a.35435
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalizing devitalized bone allografts through polymer‐mediated short and long term growth factor delivery

Abstract: According to 5- and 10-year clinical follow-up studies large-scale bone allografts have a high failure rate, largely due to poor allograft incorporation with adjacent bone and subsequent poor remodeling. The goal of this study was to develop a methodology to deliver growth factors from large-scale bone allografts in a temporally controlled manner. Intact long bone allografts were coated with a micron-scale thick layer of degradable polymer that maintained inherent pore structures and acted as a delivery vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Given this, we have developed a method through which a thin, polymeric coating capable of retaining and delivering growth factors is applied to all surfaces of large‐scale structural allografts, with the intention of delivering therapeutic molecules capable of enhancing bone‐allograft healing. We have previously demonstrated the ability to deliver either VEGF or BMP‐2 with two distinct delivery kinetics; short‐ and long‐term . Our studies demonstrated that BMP‐2 released from the polymer‐coated allograft resulted in robust bone formation in a rat segmental defect.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Given this, we have developed a method through which a thin, polymeric coating capable of retaining and delivering growth factors is applied to all surfaces of large‐scale structural allografts, with the intention of delivering therapeutic molecules capable of enhancing bone‐allograft healing. We have previously demonstrated the ability to deliver either VEGF or BMP‐2 with two distinct delivery kinetics; short‐ and long‐term . Our studies demonstrated that BMP‐2 released from the polymer‐coated allograft resulted in robust bone formation in a rat segmental defect.…”
mentioning
confidence: 78%
“…To address these concerns, we have developed a novel procedure where a very thin coating of degradable polymer has been added to the surface of long bone allografts and loaded with relevant growth factors such that they elute with a temporal precision shown to benefit bone repair . By modifying an implant that is clinically viable and currently used in regular practice, and using materials and molecules that have long track records of safety and efficacy, we believe our approach may be accepted in the clinic, and by applying this to a known clinical challenge by directly addressing the issues at the heart of the challenge, we believe this approach has the potential to be an important tool to the orthopedic surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of attempts to develop alternative drug delivery formulations have been made to minimize unfavorable side effects and to optimize the remedial effects of BMP2 810 . Generally, BMP2 can be loaded in drug delivery formulations by simple mixing (physical adsorption via non-covalent bonding).…”
Section: Introductionmentioning
confidence: 99%